Design of Axial Flux Generator for Vertical Wind Turbine Power Plant - Adi kurniawan saputro; Riza Alfita; Oryza Sativa Nugroho; Achmad Fiqhi Ibadillah; Kunto Aji Wibisono (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
This research discusses the design and testing of an axial flux generator using neodymium iron boron (NdFeB) permanent magnets for use in vertical wind turbines at low wind speeds. The main objective of the research is to create a generator design that is compact, efficient, and can work well in low wind speed conditions. The development method begins with calculating the number of poles, coils, windings, and the maximum magnetic field. Next, 2D and 3D designs of the rotor and stator are made with a configuration of 6 pairs of poles or 12 magnets and 9 three-phase coils with a design capacity of 100 watts. After the design is completed, tests are carried out using resistor loads and various lamps to measure the generator's performance. The test results show that the generator is able to produce different efficiencies depending on the load and rotational speed. In the test using a resistor, the highest efficiency was achieved at 89.5% at a speed of 402.8 RPM, while in the test with a lamp load, the electrical efficiency reached 98.46% at a load of 1.5 watts at a speed of 1501 RPM. However, efficiency tends to decrease at higher loads due to increased copper losses in the windings. In conclusion, the designed axial flux generator is effective for use in vertical wind turbines at low speeds, although it still requires design improvements to maintain stable performance at high loads.